PF-22 Reproductive Disorder in Cows: Data Analisys of UPSUS SIWAB in Lima Puluh Kota District, 2017 - Eka Oktarianti (Hemera Zoa, 2018)
The Ministry of Agriculture has declared Upaya Khusus Sapi Indukan Wajib Bunting (Upsus Siwab) to optimizing the potential of breeding cows and increase population (Ministry of Agriculture 2016). The success of Upsus Siwab program depends on a number of areas, namely land availability, decreased reproductive disorder, availability of frozen semen, availability of liquid N2, competent inseminator, and rescue of productive females (Ministry of Agriculture 2016). Animal health plays an important role in supporting the success of population increase [1], so that reproduction disorder activities are among the activities that contribute to the success of the Upsus Siwab program.                The implementation of reproductive disorder in Upsus Siwab is reported through the Integrated National Animal Health Information System (ISIKHNAS). The data can be a source of information to assess the performance results of animal health officers and to know the proportion of cured and pregnant cows after reproductive disorders are handled.                This paper aims to study the incidence of reproductive disorders on cows in Lima Puluh Kota District in 2017. The results of these studies are expected to serve as a basis for policy making for subsequent activities.